Effect of swim bladder matrix treated with hyaluronic acid on wound healing: an animal model evaluation. (2nd April 2019) - Jalali, Sajedeh; Fereidoni, Masoud; Shahri, Nasser Mahdavi; Lari, Roya
Abstract : Objective: To investigate the potential restorative effects of the white fish ( Rutilus frisii kutum ) swim bladder matrix (FSBM) treated with hyaluronic acid (HA) in the repair of skin wounds in an animal model. Method: Wistar rats were used to investigate the repair function of FSBM as a biological scaffold. Rats were given four round wounds on their back. Wounds were divided into four groups: control, acellular fish swim bladder matrix (AFSBM), HA and AFSBM impregnated with HA (AFSBM-HA). Macroscopic and histological studies in wound healing were investigated on days three, five and seven after injury. Results: The AFSBM-HA group showed a rapid reduction in wound area compared with the other groups, indicating faster wound healing (p<0.001). At day seven after injury, the AFSBM group showed a faster process in epidermal layer formation and angiogenesis compared with the control group (p<0.001). In the AFSBM-HA group, in addition to the reduction of inflammatory cells density, a significant increase in the number of fibroblast cells and collagen synthesis was observed. An elevation in collagen synthesis and angiogenesis was also observed in the HA group compared with the control group. Conclusion: The findings of this study indicate that AFSBM-HA can potentially be used as a biological dressing in wound healing.